Meje rasti, ocena tisočletja, indeks okoljske trajnosti in indeks okoljske uspešnosti - Kirn, Andrej (Teorija in praksa, 2006)
The author compares the following studies: Limits to Growth (LTG), Millennium Assessment (MA), Environmental Sustainability Index (ESI) and Environment Performance Index (EPI). All the studies ignore the impact that the modern capitalist form of property and production has on nature/environment. Except the LTG study, all the other studies are embedded within the economic growth paradigm. The computer scenarios in the MA study do not lead to a dramatic decline of human welfare caused by changes in ecosystems assigned to economic growth. The reason for such an outcome in the MA study is that no account was taken of limitations of ecosystems and their services which cannot sustain permanent economic growth. This is the basic difference between the LTG and the MA study. The ESI and EPI studies are more management-oriented than the LTG one even though the former two studies also stress the need for a change and steps towards an eco-social sustainable society. All the measures of the MA, EPI and ESI are implicitly in line with the notion that reduction or even prevention of the degradation of nature can be achieved within the paradigm of growth and capital. Only the LTG study presupposes the most reformed eco-capitalism i.e. non-growing capital.
Keywords: Limits to growth; Meje rasti; Ecosystem; Ekosistem; Sustainable development; Trajnostni razvoj; Ekologija; Ecology; Economic growth; Ekonomska rast; Kapital; Capital; Das Kapital; družba; society